Effects of Automated Messages on Internet Users Attempting to Access "Barely Legal" Pornography. (February 2022) - Prichard, Jeremy; Wortley, Richard; Watters, Paul A.; Spiranovic, Caroline; Hunn, Charlotte; Krone, Tony
With the increasing number of individuals accessing online child sexual exploitation material (CSEM), there is an urgent need for primary prevention strategies to supplement the traditional focus on arrest and prosecution. We examined whether online warning messages would dissuade individuals from visiting a honeypot website purporting to contain barely legal pornography. Participants ( n = 419) seeking the site were randomly assigned to one of five conditions; they went straight to the landing page (control; n = 100) or encountered a warning message advising of the potential harm to viewers ( n = 74), potential harm to victims ( n = 65), ability of police to track IP addresses ( n = 81), or possible illegality of such pornography ( n = 99). We measured the attempted click-through to the site. Attrition rates for the warning message conditions were 38% to 52%, compared with 27% for the control group. The most effective messages were those that warned that IP addresses can be traced (odds ratio [OR] = 2.64) and that the pornography may be illegal (OR = 2.99). We argue that warning messages offer a valuable and cost-effective strategy that can be scaled up to help reduce the accessing of CSEM online.